Brief Report: Suboptimal Lopinavir Exposure in Infants on Rifampicin Treatment Receiving Double-dosed or Semisuperboosted Lopinavir/Ritonavir: Time for a Change. (1st May 2023) - Jacobs, Tom G.; Mumbiro, Vivian; Chitsamatanga, Moses; Namuziya, Natasha; Passanduca, Alfeu; Domínguez-Rodríguez, Sara; Tagarro, Alfredo; Nathoo, Kusum J.; Nduna, Bwendo; Ballesteros, Alvaro; Madrid, Lola; Mujuru, Hilda A.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Although super-boosted lopinavir/ritonavir (LPV/r; ratio 4:4 instead of 4:1) is recommended for infants living with HIV and receiving concomitant rifampicin, in clinical practice, many different LPV/r dosing strategies are applied due to poor availability of pediatric separate ritonavir formulations needed to superboost. We evaluated LPV pharmacokinetics in infants with HIV receiving LPV/r dosed according to local guidelines in various sub-Saharan African countries with or without rifampicin-based tuberculosis (TB) treatment. Methods: This was a 2-arm pharmacokinetic substudy nested within the EMPIRICAL trial (#NCT03915366). Infants aged 1–12 months recruited into the main study were administered LPV/r according to local guidelines and drug availability either with or without rifampicin-based TB treatment; during rifampicin cotreatment, they received double-dosed (ratio 8:2) or semisuperboosted LPV/r (adding a ritonavir 100 mg crushed tablet to the evening LPV/r dose). Six blood samples were taken over 12 hours after intake of LPV/r. Results: In total, 14/16 included infants had evaluable pharmacokinetic curves; 9/14 had rifampicin cotreatment (5 received double-dosed and 4 semisuperboosted LPV/r). The median (IQR) age was 6.4 months (5.4–9.8), weight 6.0 kg (5.2–6.8), and 10/14 were male. Of those receiving rifampicin, 6/9 infants (67%) had LPV Ctrough <1.0 mg/L compared with 1/5 (20%) in the control arm. LPV apparent oral clearance was 3.3-fold higher for infants receiving rifampicin. Conclusion: Double-dosed or semisuperboosted LPV/r for infants aged 1–12 months receiving rifampicin resulted in substantial proportions of subtherapeutic LPV levels. There is an urgent need for data on alternative antiretroviral regimens in infants with HIV/TB coinfection, including twice-daily dolutegravir.